EFFORTS TO IMPROVE STUDENT’S SELF-CONFIDENCE THROUGH THE STUDENT TEAMS ACHIEVEMENT DIVISIONS METHOD - Muhammad Istiqlal; Curie Putri Hijrihani (Universitas Mercu Buana Yogyakarta, 2020)
This research was conducted based on the problems that occur in the field, namely the low self-confidence of students. The subjects of this study were students of class VII B SMP Negeri 3 Depok consisting of 32 students. This study aims to increase student’s self-confidence in mathematics learning especially in basic competencies using algebraic concepts in solving simple social arithmetic problems. Improvement of student achievement and self-confidence is sought by applying the STAD type cooperative learning model in the learning process.The type of research used is Classroom Action Research (CAR). This classroom action research was carried out in 2 cycles. Each cycle consists of 3 meetings, where 2 meetings are used for the learning process and 1 meeting is used for evaluation tests. Data collection tools used are observation sheets, test questions, questionnaire sheets, and documentation.The results of the study showed that the STAD cooperative learning model had confidence in students of class VII B SMP Negeri 3 Depok. The percentage of students' confidence in the first cycle was 68.9% with moderate qualifications. The percentage of students' confidence in the second cycle was 71.1% with high qualifications and increased by 2.2%.